Study on the Fractal Dimension and Growth Time of the Electrical Treeing Degradation at Different Temperature and Moisture - Youping Fan; Dai Zhang; Jingjiao Li (Advances in Materials Science and Engineering)
The paper aims to understand how the fractal dimension and growth time of electrical trees change with temperature and moisture. The fractal dimension of final electrical trees was estimated using 2-D box-counting method. Four groups of electrical trees were grown at variable moisture and temperature. The relation between growth time and fractal dimension of electrical trees were summarized. The results indicate the final electrical trees can have similar fractal dimensions via similar tree growth time at different combinations of moisture level and temperature conditions.